Solidification sequence of CrMnFeCoCu dual-FCC multicomponent alloy. (1st July 2023) - Katsube, Ryoji; Luo, Litian; Nakano, Keita; Narumi, Taka; Yasuda, Hideyuki
Abstract: Multicomponent and multi-phase alloys derived from the CrMnFeCoNi alloy are receiving increasing interest in the field of structural materials. Such materials have large degrees of freedom compared with conventional alloys, therefore, their solidification sequence can be more complex. Herein, the solidification sequence of the CrMnFeCoCu alloy, where Ni in the CrMnFeCoNi alloy is substituted with Cu, was investigated using synchrotron X-ray radiography and X-ray diffraction. This study demonstrated that the microstructure composed of two phases with face-centered-cubic (FCC) structures was not simply formed through the conventional multiphase solidification manner. The uniform liquid phase first splits into two liquid phases, and they individually solidify into the two FCC solid phases. The massive-like body-centered-cubic (BCC) to FCC transformation for one of the solid phases was also confirmed. Understanding the liquid-liquid phase separation and the solid-phase transformation identified in this study can be useful for controlling the microstructure of multicomponent and multi-phase alloys. Graphical abstract: Image, graphical abstract